PSYCHOLOGICAL AND PEDAGOGICAL FEATURES OF THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE OFFICERS OF LAW ENFORCEMENT ACTIVITIES OF THE ARMED FORCES OF UKRAINE IN THE CONDITIONS OF UNDERGRADUATE - Близнюк, В. (Київський національний університет імені Тараса Шевченка, 2021)
The article substantiates the psychological and pedagogical features of the process of professional training of future law enforcement officers of the Armed Forces of Ukraine in a bachelor's degree. It is established that the professional training of future law enforcement officers is gradually moving to the readiness of the future officer to perform professional tasks. It is specified that the educational process in military institutions of higher education takes place in conditions of contradictions between new constantly growing requirements to the modern level of training of future officers and insufficient traditional level of training, between creative level of teaching and reproductive character of training which can be solved by introduction of new innovative technologies. and teaching methods. It has been determined that the process of formation of knowledge, skills and professional skills of future law enforcement officers should be based on two main stages: problem-subject, during which there is a primary perception and understanding of the content and experience of further professional activity; value-regulatory, according to which the formation of team skills and professional skills of the future officer, the development of creative style, the formation of motives, values, leadership qualities, etc. Psychological components that affect the training of future officers are identified: motivation to learn, emotional and volitional personality traits of the future officer, intellectual readiness to solve professional tasks, formed skills and abilities to perform professional tasks, a set of personal and professional qualities of the future officer, reflex. It is determined that the level of professional training of future law enforcement officers is determined by the degree of their activity as a subject, features and opportunities to independently organize their actions, behavior, activities in general on the basis of intellectual readiness and awareness of personal and professional tasks, including professional tasks. Including the ones on a tactical level.

Обґрунтовано психолого-педагогічні особливості процесу професійної підготовки майбутніх офіцерів правоохоронної діяльності ЗСУ в умовах бакалаврату. Встановлено, що професійна підготовка майбутніх офіцерів правоохоронної діяльності поступово переходить до готовності майбутнього офіцера виконувати поставлені професійні завдання. Уточнено, що освітній процес у військових закладах вищої освіти проходить в умовах суперечностей між новими постійно зростаючими вимогами до сучасного рівня підготовки майбутніх офіцерів і недостатнім традиційним рівнем підготовки, між творчим рівнем викладання і репродуктивним характером навчання, які можливо розв'язати шляхом впровадження нових інноваційних технологій та методик навчання. З'ясовано, що в основу процесу формування знань, вмінь та професійних навичок майбутніх офіцерів правоохоронної діяльності має бути покладено два основні етапи: проблемно-предметний, під час якого відбувається первинне сприйняття та осмислення змісту і досвіду подальшої професійної діяльності; ціннісно-регуляційний, за яким відбувається формування командних навичок і професійних вмінь майбутнього офіцера, відбувається розвиток творчого стилю, формуються мотиви, ціннісні орієнтації, лідерські якості тощо. Виокремлено психологічні компоненти, які впливають на професійну підготовку майбутніх офіцерів: умотивованість до навчання, емоційно-вольові властивості особистості майбутнього офіцера, інтелектуальна готовність до вирішення професійних завдань, сформовані вміння та навички виконання професійних завдань, сукупність особистісно-професійних якостей майбутнього офіцера, рефлективність. Визначено, що рівень професійної підготовки майбутніх офіцерів правоохоронної діяльності обумовлено мірою їхньої активності як суб'- єкта, особливостями та можливостями самостійно організовувати свої дії, поведінку, діяльність загалом на основі інтелектуальної готовності й усвідомлення значущості особистих і способів розв'язування професійних завдань, у тому числі, тактичних.
ПСИХОЛОГО-ПЕДАГОГІЧНІ ОСОБЛИВОСТІ ПРОЦЕСУ ПРОФЕСІЙНОЇ ПІДГОТОВКИ МАЙБУТНІХ ОФІЦЕРІВ ПРАВООХОРОННОЇ ДІЯЛЬНОСТІ ЗБРОЙНИХ СИЛ УКРАЇНИ В УМОВАХ БАКАЛАВРАТУ
Keywords: model; professional training; law enforcement officers; Armed Forces of Ukraine; military institution of higher education; модель; професійна підготовка; офіцери правоохоронної діяльності; ЗСУ; військовий заклад вищої освіти